The Impact of Prolonged Sitting Ergonomic Exposure at Work on Office Workers' Sleep Quality: A Recent Scientific Review - Nusasenjaya, Radite; Pande, Ivanna Jacklia; Alisha Putri, Safira Khalda; Nugraha, Zidan Rizqi Adi (FIRM Journal of Management Studies, 2024)
Unergonomic sitting positions and prolonged sitting duration can negatively impact workers' sleep quality and productivity. Various studies indicate that extended sitting is associated with sleep disorders, including obstructive sleep apnea (OSA), decreased heart rate variability, and an increased risk of other chronic diseases. To address these issues, ergonomics-based interventions—such as active workstations, dynamic work patterns, and increased physical activity during working hours—are recommended. Recent scientific literature highlights the importance of implementing strategies to prevent sleep disorders through interventions related to sitting posture, ultimately promoting workplace health. This aligns with the university's vision of supporting worker well-being, particularly in health, through an evidence-based approach. The findings from this review are expected to serve as a foundation for developing sustainable occupational health policies, particularly in workplace settings. This review examines the ergonomic impact of prolonged sitting on office workers' sleep quality and explores preventive measures to mitigate associated risks.